Tell me a curious (hi)story. Historical content in Vitruvius’ De architectura - Kołoczek, Bartosz Jan (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
The article examines the significance of history–themed passages (historiae) in Vitruvius’ architectural treatise De architectura and assesses their veracity vis–à–vis their rhetorical impact. The article’s particular focus lies on Vitruvius’ reflections on history, since the sound knowledge of it—as the author claims—is vital for any competent architect. It asserts that Vitruvius tends to stretch the historical truth whenever he makes an attempt at self–promotion (as an author or an architect) or seeks to win the approval of his patron emperor Augustus, to whom he dedicated his work.